Review of alien marine macrophytes in Tunisia - SGHAIER, Y. R.; ZAKHAMA-SRAIEB, R.; MOUELHI, S.; VAZQUEZ, M.; VALLE, C.; RAMOS-ESPLA, A.A.; ASTIER, J.M.; VERLAQUE, M.; CHARFI-CHEIKHROUHA, F. (Mediterranean Marine Science, 2015)
In the present study, the list of alien marine macrophytes introduced into Tunisia was updated in the light of available data and new observations. A total of 27 alien marine macrophytes have been recorded so far from Tunisia: 18 Rhodophyta, 3 Ochrophyta, 5 Chlorophyta and 1 Magnoliophyta. For each species, the locality (-ies), the year (or) period and the source of the first observation in Tunisia are given. The distribution and the status (casual, cryptogenic, established or questionable) of species in Tunisia were evaluated and, where appropriate, discussed. Among them, Hypnea cornuta is reported for the first time from Tunisia. Fourteen alien marine macrophytes are established, whereas seven cryptogenic and two casual species require further investigation. Eleven species are considered as invasive or potentially invasive in the Mediterranean Sea: Acrothamnion preissii, Asparagopsis armata, A. taxiformis Indo-Pacific lineage, Hypnea cornuta, Lophocladia lallemandii, Womersleyella setacea, Caulerpa chemnitzia, C. cylindracea, C. taxifolia, Codium fragile subsp. fragile and Halophila stipulacea. Finally, the case of four questionable species is also discussed.